2017
DOI: 10.1002/mar.20994
|View full text |Cite
|
Sign up to set email alerts
|

Examining Consumers’ Motivations to Engage in Firm‐Hosted Virtual Communities

Abstract: Consumer engagement is a complex phenomenon and understanding the underlying dynamics that facilitate its development, particularly in the virtual environment, is an important contemporary research priority due to its ability to influence value creation for customers and organizations, and because it introduces ongoing and multifaceted challenges for marketers. This research empirically tests hypotheses regarding the motivational drivers of consumer engagement with 308 members of two firm‐hosted virtual commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 130 publications
(286 reference statements)
6
57
0
1
Order By: Relevance
“…To our knowledge, prior research on ARSGs has not identified this aspect, which is somewhat surprising because one of the main ideas behind AR is changing the perception of the real word. Thus, this study extends the literature on U&GT (e.g., Claffey & Brady, ), ARSGs, and AR in general.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…To our knowledge, prior research on ARSGs has not identified this aspect, which is somewhat surprising because one of the main ideas behind AR is changing the perception of the real word. Thus, this study extends the literature on U&GT (e.g., Claffey & Brady, ), ARSGs, and AR in general.…”
Section: Discussionsupporting
confidence: 79%
“…While prior research has focused predominantly on utilitarian gratifications, this research identifies three utilitarian gratifications: sensual, social, and symbolic. These new gratifications also extend prior U&GT research, in that we introduce novel, ARSG-specific gratifications that are conceptually linked to fundamental human needs (Claffey & Brady, 2017;Katz, Haas, & Gurevitch, 1973;Rubin, 2002;Ruggiero, 2000;Sundar & Limperos, 2013).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, Mousavi, Roper, and Keeling (), who also use structural equation modeling but based on data derived from a sample of 752 US residents who self‐identified as current members of online brand communities, investigate the intermediate mechanisms mediating and moderating members’ social identity effects on brand commitment, and how this leads to positive word‐of‐mouth and resistance to negative word‐of‐mouth, for both posters (i.e., those writing review comments) and lurkers (those not writing any comments). Similar to Claffey and Brady () who also highlight the importance of social bonds and affective states, their study reveals that the affective component of social identity is an important driver of members’ commitment to the brand, to talking about the brand positively and to resisting negative comments from others. They suggest that companies can gain a competitive advantage when customers’ self‐concepts are linked to the community as competitors will find it difficult to replicate such bonds.…”
Section: Introduction To the Special Issuesupporting
confidence: 71%
“…In the first of nine articles, Claffey and Brady (), using structural equation modeling and hierarchical moderated linear regression on a sample of 308 survey respondents, study motivational drivers of consumer engagement with firm‐hosted virtual communities, to identify antecedents, influences, and outcomes, contributing to our understanding of how virtual communities engage consumers (e.g., to cocreate new products). Their study highlights that firms should design their virtual communities to facilitate knowledge sharing, provide social support, deliver an enjoyable and useful experience, and to enable consumers to cocreate, paying special attention to the need to enhance social bonds between members, particularly as their study shows that, in firm‐hosted communities, consumers’ affective states act as a moderating influence in the relationship between their cognitive appraisal and participation in, and value cocreation from, the community.…”
Section: Introduction To the Special Issuementioning
confidence: 99%